Faktor-Faktor yang Mempengaruhi Mahasiswa Akuntansi Fakultas Ekonomi UNTAN Dalam Pemilihan Karir Menjadi Akuntan PublikFaktor-Faktor yang Mempengaruhi Mahasiswa Akuntansi Fakultas Ekonomi UNTAN Dalam Pemilihan Karir Menjadi Akuntan Publik - B41111077, Samsu Aulian B41111077 aulian (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Samsu Aulian Universitas Tanjungpura Â  ABSTRACT The purpose of this study is to find and analyzes the factors that affect students accounting the economics faculty of untan in career choice become public accountant .The factors that affect career choice become public accountant can be measured with a variable salary or financial award , professional training , the social values , work environment , consideration labor market and the intrinsic value the work Population in research this is a student accounting an undergraduate degree the economics faculty of Universitas Tanjungpura Pontianak.The technique samples use proportional random sampling.Samples to research this is a student accounting economics faculty regular A and B start of the 2011, 2012, 2013, 2014 and 2015 as many as 100 respondents.Data collection done through the distribution of kuisoner to students accounting the economics faculty of universitas tanjungpura pontianak..Data analysis in this research using analysis of multiple regression by using spss version 22. Which a conclusion can be obtained from this research is work environment significant to career choice college students to be public accountant. Variable salary or award financial, professional training, the social values, consideration labor market and intrinsic value the work is not significant to career choice college students to be public accountant. Keywords: career choice be public accountant , salary or award financial , professional training , the social values , work environment , consideration labor market , intrinsic value work Â